Implementation and Validation of a New Combined Model for Outdoor to Indoor Radio Coverage Predictions - Flipo Paul; Villemaud Guillaume; Gorce Jean-Marie; Lai Zhihua; de la Roche Guillaume; Zhang Jie (EURASIP Journal on Wireless Communications and Networking, 2010)
A new model used to compute the outdoor to indoor signal strength emitted from an outdoor base station is presented. This model is based on the combination of 2 existing models: IRLA (Intelligent Ray Launching), a 3D Ray Optical model especially optimized for outdoor predictions, and MR-FDPF (Multiresolution Frequency Domain ParFlow), a 2D Finite Difference model initially implemented for indoor propagation. The combination of these models implies the conversion of the ray launching paths on the border of the buildings, into virtual source flows that will be used as input for the indoor model. The performance of the new combined model is evaluated via measurements at 2 frequencies (WiMAX and WiFi). This solution appears to be efficient for radio network planning, in term of both accuracy and computational cost.